2019
DOI: 10.29392/joghr.3.e2019073
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the implementation of Global Polio Eradication Initiative in low- and middle-income countries: a qualitative evidence synthesis

Abstract: Back Background ground The World Health Organization's Global Polio Eradication Initiative (GPEI) has succeeded in reducing the cases of Polio by 99%. The persistence of the remaining 1% in Pakistan, Afghanistan and Nigeria has continued to pose threats to polio-free neighbouring countries. This systematic review aims to contribute to ongoing efforts to eradicate polio by exploring factors that influence the successful implementation of the GPEI in low-and middle-income countries. Methods Methods We reviewed q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Experts argue that in-depth experiences of participants involved in any intervention are critical for the improvement of the said service [5] and this harnesses the strength of qualitative findings. In view of this, a QES regarding the successful implementation of GPEI in lowand middle-income countries was conducted by Mshelia et al in 2019 [6], and this identified relevant barriers and facilitators regarding polio eradication.…”
mentioning
confidence: 99%
“…Experts argue that in-depth experiences of participants involved in any intervention are critical for the improvement of the said service [5] and this harnesses the strength of qualitative findings. In view of this, a QES regarding the successful implementation of GPEI in lowand middle-income countries was conducted by Mshelia et al in 2019 [6], and this identified relevant barriers and facilitators regarding polio eradication.…”
mentioning
confidence: 99%